Two Georgian fathers: diverse in experience, united in grief. Issue 2 (1st December 2008) - James, R M; Williams, A N
Abstract : The history of paediatrics and child health is increasingly recognised to be about children themselves and how they and their families cope and adapt to their medical condition rather than about medical practitioners and august institutions. This article considers two case studies, showing how two Georgian fathers cared for their children when sickness struck and their reactions when the children died. Davies (Giddy) Gilbert, FRS (1767–1840), was a member of Parliament first for Helston and later for Bodmin. (He married Ann Mary Gilbert in 1808 and formally changed his name to Gilbert; the change received royal approbation in January 1817.) Gilbert recorded the birth and development of his son Charles (1810–1813), in one of the very earliest developmental chronicles. He regularly recorded his child's progress, including height, weight, social interaction, communication skills and speech. Apparently in good health for most of his life, Charles developed an acute abdominal disorder and died unexpectedly. John Tremayne (1780–1851) was a member of Parliament for Cornwall. His son Harry (1814–1823) had increasing bilious attacks, headaches and a squint from the age of 6 years, and died despite the best medical advice available. Current medical opinion would presume an intracranial tumour. Tremayne graphically expressed his pain as he closely observed his son suffer, apparently as much from the treatments as from the disease itself. This study sheds light on clinical aspects of Georgian medical practice, the medical marketplace and the nature of relationships between these fathers and their children.